RANCANG BANGUN PENCACAH LIMBAH TANDAN KOSONG SAWIT (Elaeis guineensis Jacq.) - Muhammad Iqbal Abdi Lubis; Andasuryani; Fadli Irsyad (Jurnal Agro Fabrica, 2020)
Agriculture’s waste is still minimum to utilized the one is empty fruit bunches (EFB), as like happened in the PT.XYZ (Xxx Yyy Zzz). EFB usually left rot into compost naturally which is need decomposition period 6 – 12months. This research aims to design chopper of EFB and carry out a technical examination of the toolperformance. Testing performed by using 5 kgs EFB at three repetition with the average of water content andfat content respectively 32.06 % and 7.46 %. The average of effective work capacity 81.46 kg/hr, chopped 43.33%, percentage do not chop 54.00 %, percentage of yield loss 2.67 %, measure the thickness of the chopping 0.5– 1 cm, 1 – 5 cm, 5 – 10 cm, and >10 cm consecutively was 64.53 %, 15.40 %, 9.21 %, and 10.85 %, therotational frequency 1,121 rpm, and noise level of chopper between 91.17 to 94.40 dB. Chopping use thischopper of EFB was 13 times more efficient than manual chopping and this research is still valid whencompared to the 2018 study.